2015
DOI: 10.1089/cyber.2014.0494
|View full text |Cite
|
Sign up to set email alerts
|

Abuse Characteristics and Psychiatric Consequences Associated with Online Sexual Abuse

Abstract: The current study examined the rate and psychiatric correlates of sexual abuse involving the use of digital technologies by the offender in a wide sample of juvenile victims. Sociodemographic, abuse, and psychiatric characteristics of 662 sexually abused children and adolescents were evaluated. Of these, 93 reported that digital devices were used by the offender in several ways to facilitate the sexual abuse. The offender-victim relationship was initiated through the Internet in 39 victims. Involvement of digi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 12 publications
3
9
0
Order By: Relevance
“…We believe that such gender differences should be considered when planning interventions for adolescents in countries where gender stereotypes are more prevalent (e.g., Chile). Consistent with previous evidence, the results of this study showed that the more frequent the OSA, the greater the symptomatology exhibited by affected adolescents in all measures provided (Houck et al, 2014;Nur Say et al, 2015;Wells & Mitchell, 2007). This finding reinforces the significance of preventing OSA, given its impact on adolescents despite the absence of physical contact with the perpetrator.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We believe that such gender differences should be considered when planning interventions for adolescents in countries where gender stereotypes are more prevalent (e.g., Chile). Consistent with previous evidence, the results of this study showed that the more frequent the OSA, the greater the symptomatology exhibited by affected adolescents in all measures provided (Houck et al, 2014;Nur Say et al, 2015;Wells & Mitchell, 2007). This finding reinforces the significance of preventing OSA, given its impact on adolescents despite the absence of physical contact with the perpetrator.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the consequences of OSA, there is a belief that this type of abuse is harmless for its victims because there is no victimization outside the online world (Whittle et al, 2013). On the contrary, the findings of different studies suggest that even when victimization occurred exclusively in the online context, victims presented a series of internalizing symptoms, such as depression and post-traumatic stress (Nur Say et al, 2015;Wells & Mitchell, 2007), and externalizing symptoms, such as antisocial behavior, substance abuse, and academic and social maladjustment (Houck et al, 2014). This finding highlights the need to prevent OSA and treat its consequences (UNICEF, 2011).…”
mentioning
confidence: 99%
“…These are known in different regions internationally as indecent images of children (IIOC), child abuse images online (CAIO), child sexual abuse material (CSAM, in recognition that what is shared may not always be visual) or, more controversially, child 'pornography'. However, technology also provides increased ease of access to initiate, blackmail, escalate and maintain abuse (Hamilton-Giachritsis, Hanson, Whittle, & Beech, 2017;Mitchell, Finkelhor, Jones, & Wolak, 2010;Say, Babadagi, Karabekiroglu, Yuce, & Akbas, 2015). Alongside the increase in TA-CSA (also known as 'online CSA'), there has been a slow realisation that there are differences to offline child sexual abuse (CSA) that may require different approaches from organizations (Martin, 2015;Svedin, 2009;Quayle, 2016).…”
Section: Professionals' Perceptions Of Risk and Impact On Children An...mentioning
confidence: 99%
“…Say et al . () examined the medical records of 662 sexual abuse victims referred from the court between 2012 and 2013 to a child and adolescent clinic in Turkey. Of these, 93 reported: (a) online/offline sexual acts through e‐mail, mobile phones, text messages and internet sites; (b) an image of the victim of a sexual nature or of the sexual abuse itself recorded on a mobile phone/camera, with threats of distribution if s/he did not continue sexual acts; (c) the image was shared online/offline; and (d) the victim was subjected to online harassment or offline sexual abuse by other offenders who knew about the image (p. 334).…”
Section: Introductionmentioning
confidence: 99%